2010
DOI: 10.1186/1476-0711-9-28
|View full text |Cite
|
Sign up to set email alerts
|

Fungal colonization in patients with chronic respiratory diseases from Himalayan region of India

Abstract: BackgroundWe screened patients with chronic respiratory diseases for microbiological and serological evidences of fungal colonisation; in order to determine its prevalence in this group of patients, examine potential clinical and radiological predictors of fungal colonisation and characterise fungal agents associated with individual diseases.MethodsBAL samples from 60 consecutive patients were subjected to microscopy and culture for fungal agents. Serum samples were analysed for precipitin antibodies to Asperg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 13 publications
7
23
2
Order By: Relevance
“…Fungal infections have recently emerged as a world-wide health care problem, owing to extensive use of broad spectrum antibiotics, immunosuppressive agents and increasing population of terminally ill and debilitated patients [1]. Aspergillus infection is the commonest invasive fungal infection which involves respiratory tract.…”
Section: Introductionmentioning
confidence: 99%
“…Fungal infections have recently emerged as a world-wide health care problem, owing to extensive use of broad spectrum antibiotics, immunosuppressive agents and increasing population of terminally ill and debilitated patients [1]. Aspergillus infection is the commonest invasive fungal infection which involves respiratory tract.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 60 consecutive patients with chronic lung diseases required bronchoscopy. Interestingly, the authors found that Aspergillus and Candida preferentially infected patients with bronchogenic carcinoma and tubercular sequelae (18).…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus was the predominant species isolated in BALF culture from six (14.2%) patients. In 2010, Biswas et al screened patients with chronic respiratory diseases for microbiological and serological evidences of fungal colonization (18). A total of 60 consecutive patients with chronic lung diseases required bronchoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The problem of fungal infections became serious in 1960s, when wide-spectrum antibiotics and cytostatic agents entered widespread use [1]. Aspergilli cause a wide range of human ailments depending on the immune status of the host [2].…”
Section: Introductionmentioning
confidence: 99%